Investigando a eficiência de uma unidade de ensino potencialmente significativa para o ensino de integrais múltiplas mediadas por tecnologias digitais. - Schmidt, Luis Felipe Tatsch (2019)
The present research developed within the Postgraduate Program in Mathematical Education and Physics Teaching, Master's level, at the Federal University of Santa Maria, the purpose was to develop, implement and evaluate a Potentially Significant Teaching Unit (PSTU) for teaching and learning the concept of multiple integrals in the application of volume, mass and mass center calculations of hypothetical parts in a Mechanical Engineering class. The research, with a quantitative-qualitative approach was classified as a case study with regard to the technical procedures and had as theoretical support David Ausubel's Theory of Meaningful Learning. In the first part of the research, a diagnostic test was carried out, with 60 students from a B Calculus class, subjects of the research. This test aimed to verify the previous knowledge that they had anchored in their cognitive network. The second part. The second part was a vídeo development made by the academics. For their analysis we based on the Digital Mathematical Performances (DMP), which is based on teaching and learning means of various mathematical contents, through the arts and digital media. Where we can conclude that bringing a different approach from the traditional to the discipline has brought significant learning evidence for understanding the content of multiple integrals.